Political Connection And Capital Structure Deviation: The Interaction Role Of Corporate Governance Mechanisms On The China’s Listed Construction Firms - Hu, Xiang (2023)
China's political-economic system allows the government to have a dominant position in the economy and absolute control over a significant number of natural and economic resources. Chinese firms are thus eager to establish a political connection with the government to obtain superiorities in the market. The influence of political connection on capital structure deviation has been scarcely studied. The Chinese construction industry has the highest average debt ratio among all Chinese sectors, and as the representatives of China's construction firms, China's listed construction firms also have the highest average debt ratio compared with all other listed firms. In addition, over 70% of China's listed construction firms have a political connection. Thus, the study's first objective is to investigate whether the actual capital structures of China's listed construction firms deviate from their optimal levels. The second objective is to examine the relationship between political connection and capital structure deviation by using the data of China's listed construction firms from 2010 to 2019. The third objective is to explore the interaction effect of corporate governance mechanisms on the relationship between political connection and capital structure deviation. This research uses fixed-effect model to analyze the data. The first finding shows that almost all of China's listed construction firms have a positive deviation in capital structure. That is, most of China's listed construction firms are over-indebted. The positive capital structure deviation represents a higher capital cost and a lower firm value. The second finding is a significant positive relationship between political connection and capital structure deviation.